2020
DOI: 10.1038/s41467-020-19510-5
|View full text |Cite
|
Sign up to set email alerts
|

Organized cannabinoid receptor distribution in neurons revealed by super-resolution fluorescence imaging

Abstract: G-protein-coupled receptors (GPCRs) play important roles in cellular functions. However, their intracellular organization is largely unknown. Through investigation of the cannabinoid receptor 1 (CB1), we discovered periodically repeating clusters of CB1 hotspots within the axons of neurons. We observed these CB1 hotspots interact with the membrane-associated periodic skeleton (MPS) forming a complex crucial in the regulation of CB1 signaling. Furthermore, we found that CB1 hotspot periodicity increased upon CB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…It was nevertheless shown that surface diffusion of membrane components is compartmented by the submembrane actin rings along the proximal axon [65]. Moreover, the MPS is able to organize signaling from axonal membrane proteins such as CB1, L1-CAM and FGFR1/TrkB by transiently recruiting activated receptors and intracellular effectors at the center of spectrin tetramers (see above) [18 ], and live-cell imaging evidenced activated CB1 receptors immobilization at this location [36]. Beyond receptor signaling, the dense mesh of the MPS as seen on PREM images is likely to prevent endocytosis from the plasma membrane.…”
Section: Cellular Functions Of the Mpsmentioning
confidence: 98%
“…It was nevertheless shown that surface diffusion of membrane components is compartmented by the submembrane actin rings along the proximal axon [65]. Moreover, the MPS is able to organize signaling from axonal membrane proteins such as CB1, L1-CAM and FGFR1/TrkB by transiently recruiting activated receptors and intracellular effectors at the center of spectrin tetramers (see above) [18 ], and live-cell imaging evidenced activated CB1 receptors immobilization at this location [36]. Beyond receptor signaling, the dense mesh of the MPS as seen on PREM images is likely to prevent endocytosis from the plasma membrane.…”
Section: Cellular Functions Of the Mpsmentioning
confidence: 98%
“…Besides prominent biomechanical roles, MPS serves as a critical platform to maintain the correct membrane localisation of sodium channels [5,19] and surface receptors, such as receptor tyrosine kinases (RTKs) and GPCRs. [25,26,31] These surface receptors/channels were recently found to associate with MPS to form the ordered functional nanodomains, converting extracellular stimuli to elicit rapid intracellular responses, [25,26] regulating axonal diameter and axon-axon and axon-dendrite interactions. [28] These functional nanodomains extend along the axon shafts and have essential functions in healthy and diseased neurons.…”
Section: Non-autonomous Mechanisms Regulating the Periodic Actomyosin In The Axonmentioning
confidence: 99%
“…[7,16,24] Indeed, NM-II and F-actin form regular actomyosin structures, facilitating the dynamic dilation-and-contraction of axon diameter upon cargo passage [7] as well as AP conductions. [16] Moreover, MPS, together with surface G-protein-coupled receptors, [25,26] motor proteins, and cell adhesion molecules (CAMs), [25,27] forms periodic functional nanodomains, [5,26,28,29] which have profound cellular functions, [28] such as axon growth [25,26] and axial contractility. [30] There are increasing insights into the roles of these periodic functional nanodomains in regulating the plasticity of axonal actin rings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown in brain slices (Xu et al, 2013) and in living neurons (D'Este, Kamin, Göttfert, El-Hady, & Hell, 2015). Several studies have highlighted a broad range of involvements for the MPS in neuronal processes, like stabilization of axons (Hammarlund, Jorgensen, & Bastiani, 2007), electrical conductivity (Costa et al, 2020), latticelike organization of proteins (Li et al, 2020;Vassilopoulos, Gibaud, Jimenez, Caillol, & Leterrier, 2019;Xu et al, 2013;Ruobo Zhou, Han, Xia, & Zhuang, 2019), and control of axonal diameter (Costa et al, 2020;. It was established that the MPS consists of actin rings, made up of short actin filaments, capped by adducin, interconnected by α-and β-spectrin tetramers Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%